INTERNATIONALIZATION AS A STRATEGIC DIMENSION FOR THE DEVELOPMENT OF ACADEMIC INSTITUTIONS - Василь Кремень; Сергій Курбатов (National Academy of Educational Sciences of Ukraine, 2021)
The paper is devoted to the analyses of specific features of internationalization of academic research institutions, first of all at National Academy of Educational Sciences (NAES) of Ukraine. We conducted a brief observation of contemporary English language literature in the area of internationalization of academic institutions and evaluation of its effectiveness. We tried to analyze the situation with internationalization at academic institutions in situation of limited financial support and restrictions, connected with pandemic situation with COVID-19. Special stress was made on elaboration and implementation of successful strategy of internationalization with realistic, accurate and measurable dimensions of internationalization. Using as an example the Strategy of Internationalization of NAES of Ukraine, which was approved by the Presidium of NAES of Ukraine on March, 18, 2021, we observed the main dimensions of internationalization with the relevant indicators, which could be implemented in other academic institutions in Ukraine. Also, we compare some of these indicators with the indicators of internationalization at leading international university rankings (QS and THE).